EVALUATION OF LYMPHATIC FILARIASIS AFTER TWO ROUNDS OF MASS DRUG ADMINISTRATION IN LAU LOCAL GOVERNMENT AREA OF TARABA STATE NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
This study was undertaken to evaluate the effects of Mass Drug Administration (MDA) on Wuchereria bancrofti (microfilariae) after two rounds of combined Ivermectin and Albendazole distribution. A total of 221 participants were recruited in three communities in Lau Local Government Area of Taraba State by convenience sampling method. Questionnaires and physical examinations were used to assess clinical manifestations associated with the infection. Blood samples were collected by finger prick method and stained with Giemsa stain for examination to establish the presence of W. bancrofti while immunochromatographic card test was performed to determine the presence of filarial antigen in serum. Previous data were used to determine the pre-drug prevalence of the parasite. The results showed that the drug did not significantly reduce the clinical manifestations reported among the patients. The microfilariae prevalence and microfilaria mean density after two rounds of drug administration was 19.5% and 1.49%, while the pre- MDA prevalence and microfilaria mean density was 27.8% and 2.44% respectively. There was a statistically significant decrease of microfilaria prevalence (P
Keywords: Wuchereria bancrofti, Mass Drug Administration, Prevalence, clinical manifestations, microfilaria